Masalah pemakanan di kalangan murid sekolah rendah di Sarawak, 1999 - Hashami, B.; Mariah, A.; Awang Ismail, A.M.; Rasidah, A.W. (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2001)
A cross-sectional study was conducted to identify nutritional problems and factors associated with the problems amongst primary school children who received school milk program (PSS), food supplement program (RMT) and control (did not participate in any nutritional program).The study was conducted between August to December, 1999. The schools were selected from all the 9 administrative divisions by multistage random sampling. All school children who received school milk program in the selected school were taken as samples. The equal number of matched control (including RMT samples) were also selected. Data were obtained via guided interview, measurement of height, weight and haemoglobin level. A total of 2026 samples were successfully studied. Out of these, 53.8% were PSS samples, 31.0% Controls, and 15.2% RMT samples. Majority of the samples were female (52.5%),and from urban or small town schools (52.8%). The study found that the practice of not having regular breakfast was still practiced by many (18.8%), although samples who did not have food for morning break, lunch and dinner were much lower. School milk program was well accepted by most of the samples, their teachers and parents.However, majority of the samples (60.8%) drink milk occasionally (once in few months) only, although they generally like to drink milk, it is easily available affordable and come with many flavours. Anthropometric assessments showed the rate of low weight for age, low weight for height and rate of anaemia were still relatively high among samples. The nutritional problems were noted to be associated significantly with their participation in the nutritional program, age, ethnicity, geographical area, taking breakfast, and the presence of illness one month prior to the study. The findings reinforced information on the importance of continuing and expanding school milk program amongst the low socio-economic group in order to achieve better academic performance in the future.